Compaction quality assessment of rockfill materials using roller-integrated acoustic wave detection technique - Zhang, Qinglong; Liu, Tianyun; Zhang, Zhaosheng; Huangfu, Zehua; Li, Qingbin; An, Zaizhan (Automation in construction, 2019)
During conventional earth-rock dam construction, quality control and acceptance (QC/QA) are based on limited spot tests of material density at random locations which may not be representative of the compacted area and may consist of potential bias. Based on roller-integrated acoustic wave detection technique with real-time kinematic global positioning systems, this research adopted sound compaction value (SCV) as a real-time monitoring index for the dam compaction quality, and subsequently proposed an SCV-based assessment method to estimate the compaction quality of rockfill (RF) materials. Additionally, a geostatistical method (Kriging) was adopted to obtain estimates for both SCVs and compaction quality at any location on the work area, thereby calculating the qualified rate of compaction quality for the entire work area. A case study on the Qianping project in China indicates a strong linear correlation between the SCV and the compaction parameters as well as the dry density of RF materials; therefore, it can serve as a reliable index for monitoring compaction quality of RF materials. Assessment of compaction quality on the entire work area can be quickly and continuously achieved using the proposed method, which can effectively overcome the above limitation of conventional testing, timely feedback compaction information to avoid quality defects, and availably improve the construction quality of earth-rock dams. •A SCV-based assessment method suitable for rockfill materials is proposed.•A strong linear correlation exists between SCV and compaction parameters.•Different regression models provide a choice for quality estimation.•Method is verified to effectively assess quality and avoid quality defects.